Refresh (Reflection Response of Habits) Website Inovasi untuk Remaja SMP Tingkatkan Sikap Anti Bullying - Adista Nurfadillah; Tetti Solehati (Universitas Ngudi Waluyo, 2026)
Abstract Adolescents are a vulnerable population undergoing biological, cognitive, and socio-emotional transitions, which may increase the risk of involvement in bullying behavior, either as perpetrators or victims. The rising prevalence of bullying cases in Indonesia highlights the need for more systematic and preventive digital interventions. This study aims to develop a conceptual design of the REFRESH (Reflection Response of Habits) website as a digital-based anti-bullying intervention model for junior high school students. A descriptive qualitative approach with a conceptual study design was employed. System development followed the Waterfall model, including requirement analysis, system design, conceptual implementation, comparative testing, and maintenance planning. The proposed REFRESH platform integrates five core features: interactive educational content, anonymous reporting, psychological risk screening, psychological assessment, and collaboration with school counselors and healthcare professionals. Comparative evaluation indicates that REFRESH offers a more comprehensive approach than existing anti-bullying platforms by emphasizing early detection and multidisciplinary collaboration. Conceptually, the integration of these features has the potential to enhance students’ awareness, strengthen psychological safety, and support sustainable school-based interventions. Further research is required to implement the system technically and to empirically evaluate its effectiveness in improving anti-bullying attitudes and behaviors. Abstrak Remaja merupakan kelompok rentan yang mengalami perubahan biologis, kognitif, dan sosio-emosional sehingga berisiko terlibat dalam perilaku bullying, baik sebagai pelaku maupun korban. Meningkatnya kasus bullying di Indonesia menunjukkan perlunya inovasi pencegahan yang lebih sistematis dan preventif. Penelitian ini bertujuan merancang konsep website REFRESH (Reflection Response of Habits) sebagai model intervensi digital untuk meningkatkan sikap anti-bullying pada remaja SMP. Penelitian menggunakan pendekatan deskriptif kualitatif dengan studi konseptual. Pengembangan sistem dilakukan menggunakan model Waterfall yang meliputi analisis kebutuhan, desain sistem, implementasi konseptual, pengujian komparatif, dan perencanaan pemeliharaan. Hasil perancangan menunjukkan bahwa REFRESH mengintegrasikan lima fitur utama, yaitu edukasi interaktif, pelaporan anonim, skrining risiko psikologis, asesmen psikologis, serta kolaborasi dengan guru BK dan tenaga kesehatan. Evaluasi komparatif menunjukkan bahwa sistem ini lebih komprehensif dibandingkan platform anti-bullying sebelumnya karena menekankan deteksi dini dan pendekatan kolaboratif lintas profesi. Secara konseptual, integrasi fitur tersebut berpotensi meningkatkan kesadaran, memperkuat keamanan psikologis siswa, serta mendukung intervensi berkelanjutan di lingkungan sekolah. Penelitian lanjutan diperlukan untuk menguji efektivitas dan implementasi teknis sistem secara empiris.